Ultra-Tough Polylactide/Bromobutyl Rubber-Based Ionomer Blends via Reactive Blending Strategy - Zhang, Xingfang; Lu, Xu; Huang, Dong; Ding, Yingli; Li, Jinshan; Dai, Zhenyu; Sun, Liming; Li, Jin; Wei, Xiaohui; Wei, Jie; Li, Yang; Zhang, Kunyu (Frontiers in Chemistry, 2022)
A series of ultra-toughened sustainable blends were prepared from poly(lactic acid) (PLA) and bromobutyl rubber-based ionomers (i-BIIRs) via reactive blending, in which dicumyl peroxide (DCP) and Joncryl®ADR-4440 (ADR) were used as reactive blending additives. The miscibility, phase morphology and mechanical property of the PLA/i-BIIRs blends were thoroughly investigated through DMA, SEM, tensile and impact tests. The influence of different ionic groups and the effects of DCP and ADR on the compatibility between the phases, phase structure and mechanical properties were analyzed. The introduction of the imidazolium-based ionic groups and the reactive agents enable the i-BIIRs play multiple roles as effective compatibilizers and toughening agents, leading to improved interfacial compatibility and high toughness of the blends. The mechanical properties test showed that the PLA/i-BIIRs blends exhibit excellent toughness: impact strength and the elongation at break of AR-OH(30)+AD reached 95 kJ/m2 and 286%, respectively. The impact fracture surface showed the large-scale plastic deformation of the PLA matrix in the blends, resulting in greatly absorbing the impact energy. The results proved that simultaneously applying reactive blend and multiple intermolecular interactions methods is an effective toughening strategy for toughening modification of the PLA blends.